The Association Between Serum Complement 4 and Kidney Disease Progression in Idiopathic Membranous Nephropathy: A Multicenter Retrospective Cohort Study - Liu, Jing; Zha, Yang; Zhang, Peng; He, Peng; He, Lijie (Frontiers in Immunology, 2022)
Introduction: Complement system plays an important role in the pathogenesis of idiopathic membranous nephropathy (IMN), however, the relationship between serum complement 4 (C4) and kidney disease progression in IMN is unclear. This study aims to investigate the association of serum C4 level with the risk of kidney disease progression among patients with IMN. Methods: The retrospective cohort assessed 1254 participants with biopsy-proven IMN from three centers in Xi 'an, Shaanxi Province, China. Baseline serum C4 levels were measured at renal biopsy. The association between baseline serum C4 and the risk of renal function progression, defined as a 30% decline in renal function or end stage renal disease, was evaluated in Cox proportional hazards models. Results: A total of 328 patients with IMN and nephrotic proteinuria were eligible, and 11.3% (37/328) of them attained the renal function progression events after a median follow-up of 51 months (37-59 months). After adjustment for other confounders, a higher value of serum C4 was independently associated with a higher risk of renal function progression event with a hazard ratio (HR) of 4.76 (95% confidence interval [95% CI], 1.77-12.79) per natural log-transformed C4. In reference to the low level of C4, the adjusted HRs were 2.72 (95% CI, 1.02-7.24) and 3.65 (95% CI, 1.39-9.60), respectively, for the median and high levels of C4 (P for trend=0.008). Additionally, the results were robust and reliable in the sensitivity and subgroup analyses. Conclusion: Among patients with IMN and nephrotic proteinuria, serum C4 at renal biopsy is an independent predictor for kidney disease progression regardless of other confounders.